Gut bacteriome dynamics in high altitude-adapted chicken lines: a key to future poultry therapeutics - Neha R. Bhagat; Vijay K. Bharti; Geeta Shukla; Praveen Rishi; O. P. Chaurasia (Scientific Reports)
Abstract High-altitude-adapted chickens harbor a unique gut bacteriome essential for their survival under extremely cold and hypoxic environment, however, little is known about their population and functional dynamics, limiting their application in poultry production. Hence, this study employed amplicon-based metagenomics to examine the gut bacterial diversity and their functional profile in two high-altitude-adapted chicken lines, e.g. LEHBRO-1 and LEHBRO-3. The results revealed significant variations in taxonomic abundance at the phylum level, with Firmicutes, Proteobacteria, Bacteroidetes, and Actinobacteria predominating in LEHBRO-1, whereas Firmicutes, Proteobacteria, Bacteroidetes, Planctomycetes, and Actinobacteria predominated in LEHBRO-3. Genus-level diversity and Linear Discriminant Analysis Effect Size (LEfSe) biomarker analysis also substantiated the differences in the gut bacterial communities between the two chicken lines. Furthermore, functional profiling revealed enrichment of carbohydrate, nucleotide, lipid, amino acid, fatty acid, energy, and glycan metabolic pathways in the gut bacteriomes of these high-altitude chicken lines. The Statistical Analysis of Metagenomic Profiles (STAMP) for metabolic profiling identified a significant difference in purine and protein metabolism between these two chicken lines. These findings indicate the unique gut bacteriome and their functional diversity in high-altitude-adapted chickens, which would provide a foundation for future research on gut therapeutics to improve chicken health and productivity in high-altitude areas.